Associations of sociodemographic factors and body image with body weight status among Yemeni adolescents in Selangor and Putrajaya, Malaysia - Ali Mareh, Abdulwali; Ibrahim, Zuriati; Ali, Faisal; Al-Shahethi, Ahmed; Abu Saad, Hazizi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Despite the high prevalence of malnutrition in Yemen, little is known on malnourished Yemeni adolescents in Malaysia. This study aimed to assess the body weight status among Yemeni adolescents in Malaysia and its association with sociodemographic factors and body image. Methods: A cross-sectional study involving 364 Yemeni adolescents aged between 12 to 18 years were recruited from four schools in Selangor and Putrajaya, Malaysia. Sociodemographic factors and body image data were collected through face to face interview. Height and body weight were measured and body mass index (BMI) was calculated. Results: The prevalence of overweight and obesity was 23.6%, with 5.2% of thinness. Multivariable logistic regression revealed that a family income greater than RM5,001 (OR = 3.77, p = 0.004), body shape dissatisfaction (OR = 3.54, p = 0.001) and perception of overweight/obesity (OR = 5.75, p = 0.001) were associated with an increased risk of being overweight and obese. Whereas a positive perception of underweight (OR = 0.23, p = 0.009) was found to be a significant protective factor against overweight and obesity. Conclusion: Overweight and obesity are prevalent among Yemeni adolescents in Malaysia. These findings highlight the need for regular weight status assessments amongst adolescents. Additionally, an obesity intervention program that incorporates body image perception may improve the children’s body weight status.